Standard versus extended pelvic lymphadenectomy in the patients with clinically localized prostate cancer - Bogdanović, Jovo; Sekulić, Vuk; Trivunić-Dajko, Sandra; Herin, Ranko; Djozić, Senjin (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Pelvic lymph node dissection (PLND) is the most accurate staging procedure in the diagnosis of lymph node involvement by prostate cancer. However, the therapeutic value of this procedure is still unclear. The objective of the study was to compare diagnostic and therapeutic values of extended and standard PLND as an adjunct of radical prostatectomy. Methods. The patients who underwent surgical treatment for clinically localized prostate cancer (n = 157) were enrolled in this open nonrandomized prospective study. In the standard PLND (sPLND) group 109 patients were enrolled while the extended PLND (ePLND) group involved 48 patients. Both groups were compared regarding age, prostate-specific antigen (PSA) level, a percentage of positive biopsies, preoperative and postoperative Gleason score, number of retrieved and positive lymph nodes, duration of surgery, blood loss, amount of lymphorrhea and biochemical recurrence-free survival. Results. The average number of retrieved lymph nodes was 17.27 and 24.46 in the sPLND and ePLND group, respectively (p = 0.001). The rate of positive lymph nodes was 9/109 (8.3%) and 8/48 (16.7%) in the sPLND and ePLND groups, respectively. Biochemical recurrence was noted in 38/109 (31.2%) and 7/48 (14.6%) patients in the sPLND and ePLND group, respectively (p = 0.003). Conclusion. Comparison of sPLND to ePLND led to the following conclusions: nodal yield was significantly higher in the ePLND group; the ePLND template was associated with a much higher rate of lymph node metastases; the biochemical recurrence-free survival rate was significantly more favorable in the ePLND group comparing to the sPLND group.
Keywords: lymph node excision; pelvis; prostatic neoplasms; prostatectomy; surgical procedures, operative